Co-creating urban green infrastructure connecting people and nature: A guiding framework and approach. (1st March 2019) - van der Jagt, Alexander P.N.; Smith, Mike; Ambrose-Oji, Bianca; Konijnendijk, Cecil C.; Giannico, Vincenzo; Haase, Dagmar; Lafortezza, Raffaele; Nastran, Mojca; Pintar, Marina; Železnikar, Špela; Cvejić, Rozalija
Abstract: Urban green infrastructure (UGI) and nature-based solutions are increasingly recognized as instruments to address urban sustainability challenges, yet rely on a good understanding of complex social-ecological system (SES) to function adequately. Adaptive co-management (ACM), engaging a broad variety of stakeholders in collaborative learning, is an effective strategy to improve the resilience of a SES. However, ACM studies have been criticized for neglecting the urban context, while also offering little clarity on process objectives and outcomes. To address these knowledge gaps, while also drawing attention to the important issue of socially inclusive UGI development, we present a guiding framework and approach to encourage the ACM of UGI featuring two main components. Firstly, a Learning Alliance (LA) serves as an instrument for collaborative learning and experimentation across different scales. To facilitate upscaling, we propose to establish a complementary Urban Learning Lab (ULL) to facilitate a regular exchange between the LA and legitimate peripheral networks and stakeholders in the city region. Secondly, a stepwise approach to SES analysis serves to engage a representative group of stakeholders in the LAs and ULLs, and support the processes of setting LA objectives and monitoring of adaptive capacity. We illustrate our approach to the ACM of UGI with a case study of LivadaLAB in Ljubljana, Slovenia. Applying the framework and approach, we demonstrate increased adaptive capacity of the SES around UGI as indicated by: 1) improved overall stakeholder salience, in particular for previously disempowered actor groups, 2) increased number and strength of connections between stakeholders, and 3) the consideration of a broader range of sustainable development objectives by stakeholders in their daily practice. Highlights: Learning Alliances are a suitable tool for adaptive co-management. Urban Learning Labs facilitate the upscaling of co-produced knowledge. Tools for stakeholder analysis can be used to analyse adaptive capacity. The Stakeholder Monitoring Graph visualizes stakeholder empowerment over time. The collaborative learning platforms resulted in double- and triple-loop learning.